KNOWLEDGE, ATTITUDE, AND PRACTICES TOWARDS INSECTICIDE-TREATED MOSQUITO NET UTILIZATION AMONG PREGNANT WOMEN ATTENDING ANTENATAL CARE AT MASAKA REGIONAL REFERAL HOSPITAL, MASAKA DISTRICT: A CROSS-SECTIONAL SURVEY. - NAKAWOZA , CAROLINE; KASUJJA, HENRY (Student's Journal of Health Research Africa, 2024)
Background In Uganda, the Masaka district Health sector platform statistics from the Ministry of Health show malaria as the highest disease burden with 22.2%. Hence, as a result, ITNs have been well recognized there as part of the important components of Global and National malaria control policies. Objective To determine the knowledge, attitudes, and practices towards ITN utilization among pregnant women attending ANC at Masaka Regional Referral Hospital, Masaka District. Method A cross-section descriptive survey design was employed; 59 respondents were selected using a simple random sampling technique. Data was collected using a questionnaire and analyzed using frequency and percentages descriptive statistics. Results Study findings indicate majority 36(61%) knew their importance during pregnancy, 42(71.2%) knew what is correctly done before the first usage of an ITN, and some 16(27%) knew at least one of the two types of ITNs. A generally poor attitude towards ITN utilization among pregnant women was shown as up to 39(66%) didn’t like to sleep in it, 36(61%) felt bad while sleeping under it, and 41(69.5%) believed that sleeping in it is not the only way to prevent malaria. Good practices towards ITN utilization were observed as a large number of 44(74.5%) slept under it, 30(50.8%) started sleeping in it during the first trimester, and 44(75%) hung their ITNs above the bed. Conclusion In summary, there was a high level of knowledge, poor attitude, and generally good practices about the utilization of ITNs among respondents. Recommendation The government needs to ensure the motivation of pregnant women to create a culture and enhance their understanding of ITNs. Direct health education through various mediums of communication should be carried out by the health workers. Health authorities should enhance the training of volunteers and local leaders towards proper utilization of ITNs through various directed programs by experts.